Cholesterol Hydroxylating Cytochrome P450 46A1: From Mechanisms of Action to Clinical Applications - Pikuleva, Irina A.; Cartier, Nathalie (Frontiers in Aging Neuroscience, 2021)
Cholesterol, an essential component of the brain, and its local metabolism are involved in many neurodegenerative diseases. The blood-brain barrier is impermeable to cholesterol; hence, cholesterol homeostasis in the central nervous system represents a balance between in situ biosynthesis and elimination. Cytochrome P450 46A1 (CYP46A1), a central nervous system-specific enzyme, converts cholesterol to 24-hydroxycholesterol, which can freely cross the blood-brain barrier and be degraded in the liver. By the dual action of initiating cholesterol efflux and activating the cholesterol synthesis pathway, CYP46A1 is the key enzyme that ensures brain cholesterol turnover. In humans and mouse models, CYP46A1 activity is altered in Alzheimer’s and Huntington’s diseases, spinocerebellar ataxias, glioblastoma, and autism spectrum disorders. In mouse models, modulations of CYP46A1 activity mitigate the manifestations of Alzheimer’s, Huntington’s, Nieman-Pick type C, and Machao-Joseph (spinocerebellar ataxia type 3) diseases as well as amyotrophic lateral sclerosis, epilepsy, glioblastoma, and prion infection. Animal studies revealed that the CYP46A1 activity effects are not limited to cholesterol maintenance but also involve critical cellular pathways, like gene transcription, endocytosis, misfolded protein clearance, vesicular transport, and synaptic transmission. How CYP46A1 can exert central control of such essential brain functions is a pressing question under investigation. The potential therapeutic role of CYP46A1, demonstrated in numerous models of brain disorders, is currently being evaluated in early clinical trials. This review summarizes the past 70 years of research that has led to the identification of CYP46A1 and brain cholesterol homeostasis as powerful therapeutic targets for severe pathologies of the CNS.